2020
DOI: 10.3390/en13030633
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Multiple Flow Pulses on Hydraulic Fracture Network Propagation in Naturally Fractured Volcanic Rock

Abstract: Exploring engineering methods for increasing fracture network complexity is important for the development of unconventional oil and gas reservoirs. In this study, we conducted a series of fracturing experiments on naturally fractured volcanic samples. An injection method, multiple flow pulses, is proposed to increase fracture complexity. The results show that fluid leaked into the natural fracture network (NFN) when the injection rate was low (0.2 mL/min); hydraulic-fracture-dominant fracture geometry was crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Zhuang et al 11 found that the cyclic pulse water pressure could control the fracture propagation when studying the fracture propagation of granite under various pulse modes. Yang et al 12 concluded that multiple pulses can effectively create complex fracture networks and increase pore size. Parchei‐Esfahani et al 13 pointed out that fracture extension is sensitive to pressure pulse cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Zhuang et al 11 found that the cyclic pulse water pressure could control the fracture propagation when studying the fracture propagation of granite under various pulse modes. Yang et al 12 concluded that multiple pulses can effectively create complex fracture networks and increase pore size. Parchei‐Esfahani et al 13 pointed out that fracture extension is sensitive to pressure pulse cycles.…”
Section: Introductionmentioning
confidence: 99%